Zwei Monate experimentelles Arbeiten : Ausstellungen im Künstlerhaus Hamburg. (Hamburg : Künstlerhaus e.V., 1980)
Hamann, Volker ; Höpflinger, R. ; Regnier, E. ; Hoffmann, Bruno ; Kern, Marina ; Leskly, Hezy ; Liptow, Hilmar ; Mau, Jürgen ; Mol, Kees ; Pitz, Hermann ; Rüpke, Angela ; etc.
Ausstellungen im Künstlerhaus Hamburg, 1980
boek